PENGEMBANGAN BAHAN AJAR KBC BERBASIS PEMBELAJARAN 4C FIKIH KELAS II MI MIFTAHUL HUDA 2 KOTA PALANGKA RAYA - Muhammad Syabrina; Nurdiana Nurdiana; Rahma Nur Sabila; Muhammad Jefri; Ibrahimul Khalis (CV. KAMPUS AKADEMIK PUBLISING, 2026)
In the era of the industrial revolution 4.0, teaching materials need to be adapted to technological developments so that students can be interested. The type of teaching material that can attract students' interest is teaching materials in the form of interactive media. This study aims to develop digital teaching materials in the form of interactive learning media that can be used by students in grade II in learning Fiqh. This study follows the ADDIE model with five stages: analysis, design, development, implementation, and evaluation. Data were collected through interviews, observations, documentation, and questionnaires. The results of the questionnaire from material experts, design and field trials showed that this interactive learning media was appropriate, with a percentage score reaching 82.3% including the